Innate Immune Responses to Bacterial Ligands in the Peripheral Human Lung – Role of Alveolar Epithelial TLR Expression and Signalling - Thorley, Andrew J. (Public Library of Science, 2011)
It is widely believed that the alveolar epithelium is unresponsive to LPS, in the absence of serum, due to low expression of TLR4 and CD14. Furthermore, the responsiveness of the epithelium to TLR-2 ligands is also poorly understood. We hypothesised that human alveolar type I (ATI) and type II (ATII) epithelial cells were responsive to TLR2 and TLR4 ligands (MALP-2 and LPS respectively), expressed the necessary TLRs and co-receptors (CD14 and MD2) and released distinct profiles of cytokines via differential activation of MAP kinases. Primary ATII cells and alveolar macrophages and an immortalised ATI cell line (TT1) elicited CD14 and MD2-dependent responses to LPS which did not require the addition of exogenous soluble CD14. TT1 and primary ATII cells expressed CD14 whereas A549 cells did not, as confirmed by flow cytometry. Following LPS and MALP-2 exposure, macrophages and ATII cells released significant amounts of TNFα, IL-8 and MCP-1 whereas TT1 cells only released IL-8 and MCP-1. P38, ERK and JNK were involved in MALP-2 and LPS-induced cytokine release from all three cell types. However, ERK and JNK were significantly more important than p38 in cytokine release from macrophages whereas all three were similarly involved in LPS-induced mediator release from TT1 cells. In ATII cells, JNK was significantly more important than p38 and ERK in LPS-induced MCP-1 release. MALP-2 and LPS exposure stimulated TLR4 protein expression in all three cell types; significantly more so in ATII cells than macrophages and TT1 cells. In conclusion, this is the first study describing the expression of CD14 on, and TLR2 and 4 signalling in, primary human ATII cells and ATI cells; suggesting that differential activation of MAP kinases, cytokine secretion and TLR4 expression by the alveolar epithelium and macrophages is important in orchestrating a co-ordinated response to inhaled pathogens.